Fancy Nancy sees stars - O'Connor, Jane.; Preiss-Glasser, Robin; Enik, Ted (New York : HarperCollinsPublishers, 2008)
When a rainstorm prevents Nancy and her best friend, Robert, from getting to the planetarium the night of a class field trip, she has a brilliant idea for making things better.
"Beginning reading, 1."
Keywords: Astronomy -- Juvenile fiction; School field trips -- Juvenile fiction; Planetariums -- Juvenile fiction